2018
DOI: 10.1093/mnras/sty117
|View full text |Cite
|
Sign up to set email alerts
|

Not all stars form in clusters – measuring the kinematics of OB associations with Gaia

Abstract: It is often stated that star clusters are the fundamental units of star formation and that most (if not all) stars form in dense stellar clusters. In this monolithic formation scenario, low density OB associations are formed from the expansion of gravitationally bound clusters following gas expulsion due to stellar feedback. N-body simulations of this process show that OB associations formed this way retain signs of expansion and elevated radial anisotropy over tens of Myr. However, recent theoretical and obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 39 publications
8
80
1
Order By: Relevance
“…Gaia astrometry have not found evidence for expansion in other associations (e.g., Wright et al 2016;Wright & Mamajek 2018;Ward & Kruijssen 2018) The results from these studies may indicate a need to distinguish subgroups present in associations in order to detect the kinematic signatures of expansion that exist.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Gaia astrometry have not found evidence for expansion in other associations (e.g., Wright et al 2016;Wright & Mamajek 2018;Ward & Kruijssen 2018) The results from these studies may indicate a need to distinguish subgroups present in associations in order to detect the kinematic signatures of expansion that exist.…”
Section: Discussionmentioning
confidence: 74%
“…Rather, they concluded that the association was most likely formed in multiple highly-substructured subgroups, a view supported by the age distribution found by Pecaut & Mamajek (2016). Ward & Kruijssen (2018) examined kinematic parameters of 18 nearby associations and concluded that none of these associations showed signs of evolving from clusters. This new evidence implies that star formation can take place over regions of various densities and that regions of high local density form gravitationally bound clusters while low density regions form unbound associations (Kruijssen 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wright & Mamajek (2018) used the first Gaia data release to show that the Sco-Cen OB association was most likely formed in a highly substructured state with multiple small-scale star formation events rather than a single, monolithic burst of star formation. Another study of 18 nearby OB associations (although different associations to those analysed in Ward & Kruijssen 2018), using the first Gaia data release found little evidence of systematic expansion of OB associations (Mel'nik & Dambis 2017). Cantat-Gaudin et al (2018) find that, while the Vela OB2 association is expanding, the expanding stellar distribution suggests that this expansion began before the stars in Vela OB2 were formed, probably the result of a supernova.…”
Section: Introductionmentioning
confidence: 95%
“…Cantat-Gaudin et al (2018) obtain the ages and the kinematics of a sample of nearby open clusters. Ward and Kruijssen (2018) analyzing the kinematics of young OB associations, come to the conclusion that not all the stars formed in clusters. TGAS data support the idea that star formation has a hierarchical nature.…”
Section: Gaia First Data Releasementioning
confidence: 99%